Protein intake and daily activities influence to infant birth weight - Rossa Kurnia Ethasari; Sapja Anantanyu; Kusnandar Kusnandar (International Journal of Public Health Science (IJPHS), 2019)
Pregnancy is a crucial period time of life. One of the contributing factors in pregnancy is mother’s nutritional need, one of which is protein intake. A pregnant woman’s protein need must be fulfilled for the health of both mother and baby. A more active lifestyle of a pregnant woman will also induce more baby’s brain development than a less active one. To analyze the correlation between protein intake and daily activity with infant birth weight in third trimester pregnant women. Analytic observational using prospective cohort design.Independent variables are protein intake and daily activities.Protein intake data is acquired from 2x24 hours food recall, daily activity is measured using Baecke questionnaire and infant birth weight is measured using a baby scale.Sample size of this study is 109 women achieved using simple random sampling. Statistic test used was chi square test.Mean number of pregnant women’s protein intake per day is 0,68±0,469gr.Bivariate test result shows a significant correlation between protein intake and infant birth weight(p=0,000) and a sighificant correlation between daily activities and infant birth weight(p=0,000). There is a correlation between protein intake with infant birth weight in third trimester pregnant women; and there is a correlation between daily activity with infant birth weight in third trimester pregnant women.